Conceptualizing the Economic Role of the State: Laissez-Faire, Technocracy, and the Democratic Alternative - Sabeel Rahman, K (Polity, 2011)
This article contrasts three visions of political economy that appear in the writings of Keynes, Hayek, and Polanyi, and discusses their relevance to current debates over economic policy in the United States. Keynes proposed optimizing market practices through technocratic governance. In recent decades, this influential approach has proven vulnerable to the revival of Hayek's laissez-faire arguments. Polanyi, by contrast, introduced a framework that criticizes both laissez-faire conceptions and the technocratic approach pioneered by Keynes. Because of its emphasis on democratic participation, Polanyi's reasoning provides the building blocks for a new type of contemporary progressive politics.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; KEYNES, John Maynard, 1883-1946; United States; economic policy; free enterprise; government regulation; progressivism; the state